A Bibliometric Analysis the Scope of Local, Global, And Glocal Studies (Glocal Society Journal, 2024)
This article seeks to employ bibliometric analysis to offer a thorough picture of the research environment concerning local, global, and glocal contexts. Amidst the increasing globalization, it is imperative to deeply understand the interplay between local and global contexts and the "glocal" concept. This study investigates the current body of literature on these three areas by assessing patterns of publishing, trends in research, and collaborations among scientists. Using data from famous academic databases, we have found noteworthy keywords, notable authors, and esteemed publications pertaining to this topic. The research indicates a significant rise in the quantity of publications regarding local, global, and global contexts during the previous two decades. This research also illustrates a shift in focus from localized contextual examinations to a more inclusive approach that combines global and local perspectives. These findings are anticipated to offer scholars and practitioners a novel understanding of the dynamics of interaction between local, global, and glocal contexts. Moreover, these discoveries will be a significant reference for forthcoming investigations in this field.